A Clinical Evaluation of Gomutra Ghanavati in Medoroga w.s.r. to Dyslipidaemia - A Randomized Controlled Trial - Chandra Prakash; Sonika Pal; Udai Raj Saroj; Harish Bhakuni; S.M. Sharma (AYUSHDHARA, 2025)
In present scenario human lifestyle mainly includes faulty food habits, minimum physical and mental exercise, intellectual exercise with stress and depression resulting into various metabolic disorders in human being. Dyslipidaemia is one of the main metabolic diseases describing disordered lipid metabolism. Dyslipidaemia alone affects approximately 12% of global population. The clinical study was conducted in 60 clinically diagnosed patients of Medoroga (dyslipidaemia), divided into two groups (30 patients in each group). In Group A patients were administered 1gm of Gomutra Ghanavati orally after meal with lukewarm water twice a day for 60 days. In Group B patients were administered 10mg of Atorvastatin orally after meal with water once a day for 60 days. Conclusion: On the basis of their clinical manifestations “Medoroga” can be correlated with the clinical entity “Dyslipidaemia”. Gomutra Ghanavati showed highly significant results in some subjective and objective parameters Thus, it is concluded that Gomutra Ghanavati can be used as an effective and safe treatment for dyslipidaemia (Medoroga).